(untitled) (Brazilian Journal of Radiation Sciences, 2021)
The irradiation of fresh post-harvest foods has as main interests: inhibit sprouting, increase shelf life, reduce or delay damage caused by insects and diseases. This work is a preliminary study on the use of gamma radiation in fresh peas grains (Pisum sativum L.) in order to evaluate its effects on the inhibition of sprout and its increase in shelf life. The peas were submitted to 4 treatments: 0 (control), 0.15, 0.30 and 0.45 kGy, in a 60 Co research irradiator, after irradiation stored at 8 °C, being evaluated at 1, 7, 14 and 21 days after irradiation, for the following analyzes: assessments of visual appearance, total soluble solids, titratable total acidity, ratio, fresh weight loss, coloring, texture, pH, water content and ash. By visual evaluation it was observed that the irradiation did not significantly change the shelf life of the grains. The visual appearance, coloring and pH had interference due to the natural process of grain maturation. The doses of gamma radiation did not influence the content of ash, water and texture during storage and that dose of 0.45 kGy was not sufficient to inhibit the sprouting of the peas. It is possible to conclude that, with this work, a recommendation that, for the later works, in which one wishes to define the shelf life or to inhibit sprouting pea, initiate the irradiation of its samples with values above 0.45 kGy.